THE CHURCH AS AN AGENT OF POLITICAL TRANSFORMATION: A CONTEXTUAL THEOLOGICAL APPROACH IN CONTEMPORARY SOCIETY - Wilson Afandi Siahaan; Riris Johanna Siagian (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This paper examines the role of the church as an agent of political transformation through a contextual theological approach in contemporary society. Politics is not merely understood as a struggle for power but as an ethical means to realize justice, welfare, and the common good. From the perspective of Christian theology, the church's involvement in politics is part of its faith calling to manifest the signs of the Kingdom of God in the world. The church should not be trapped in pragmatic political practices but is called to play a prophetic role of rebuking injustice, defending the oppressed, and serving as the moral conscience of the nation. Through a contextual theological approach, the church can read the signs of the times and respond to socio-political realities with Gospel values ​​such as love, justice, and peace. The political transformation promoted by the church focuses on shifting the paradigm from politics of power to politics of service. The church is called to build a political ethic rooted in faith, strengthen Christian participation in the public sphere, and cultivate awareness that faith must be embodied in social praxis. In the context of a modern, pluralistic, and complex democracy, the church is expected to be a space for dialogue, a defender of justice, and a critical partner to the government in pursuing the common good. Thus, the church is not merely a spiritual entity but a transformative public force that brings the values ​​of the Kingdom of God into national life in a concrete, prophetic, and civilized manner.